Zodiac - Fincher, David, 1962-; Jake, Gyllenhaal; Robert Downey Jr; Mark Ruffalo; Brian Cox; Chloe Sevigny (Paramount USA, 2007)
Closer in spirit to a police procedural than a gory serial-killer flick, David Fincher's Zodiac provides a sleek, armrest-gripping re-invention of the crime film. It surveys the investigation of the Zodiac killings that terrorized the San Francisco Bay area in the late -60-early -70s; Zodiac not only killed people, but cultivated a Jack the Ripper aura by sending icky letters to the newspapers and daring readers to solve coded messages. But the film's focus isn't on the killer. We follow the reporters and detectives whose lives are taken over by the case, notably an addictive crime writer (a sartorially splendid Robert Downey Jr.), an awkward editorial cartoonist (Jake Gyllenhaal), and a hard-working cop (Mark Ruffalo). Fincher and his brilliant cinematographer Harris Savides are deft at capturing the period feel of the city, without laying on the seventies kitsch, and James Vanderbilt's script doles out its big moments to major and minor characters alike. Fincher's confidence is infectious; the movie glides through its myriad details with such dexterity that even the blind alleys and red herrings seem essential. The well-chosen cast includes unexpected people popping up all over: Anthony Edwards as a lunch-bucket homicide cop; Charles Fleischer as a mysterious suspect; Elias Koteas and Donal Logue as small-town policemen whose districts are hit by Zodiac; Chloe Sevigny as Gyllenhaal's sweet-natured wife; Brian Cox as the media-friendly lawyer Melvin Belli, so famous he once appeared on Star Trek; and the mighty John Carroll Lynch, as a supremely creepy suspect. The film is based on non-fiction books by Robert Graysmith (he's portrayed by Gyllenhaal), although Fincher and co. did extensive research on their own. The result is a propulsive whodunit without (thus far) an ending, but the uncertainty makes the film even more intriguing.
Based on the Robert Graysmith books about the real life notorious Zodiac, a serial killer who terrorized San Francisco with a string of seemingly random murders during the 1960s and 1970s.
Language(s): English, Turkish Subtitle(s): English, Turkish, Bulgarian, Serbo-Croatian, Slovenian
Keywords: Drama -- Crime -- Thriller; Mystery